A pilot study on red cell immunization in multiply transfused thalassaemic patients - Noor, Noor Haslina Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
BACKGROUND: The development of red blood cell (RBC) isoitnniunization with alloantibodies and autoantibodies cotnplicate transfusion therapy in multiply transfused thalassaemia patients. Thus, frequency, causes and prevention of these phenomena were studied among these patients. STUDY DESIGN AND METHODS: Clinical and serological data of 58 Malay multiply transfused thalassaemia patients who seek their treatment in 1-Iospital University Sains Malaysia were collected and analyzed prospectively. Blood samples were subjected to standard blood bank procedure for screening of antibodies and subsequent antibodies identification. All patients in our hospital received blood n1atched for only ABO and Rh (D) antigens. RESULTS: There were 46 (79.3%) patients with Hb E/f3 thalassactnia~ 8 (13.8%) f3 thalassaemia major, 3 (5.2%) J-Ib 1-1 Constant Spring and I (1.7%) Hb 1-1 disease. Overall, 8.6% of the patients had alJoantibodies and 1. 7% had autoantibodies. The alloantibodies identified were anti-E, anti-c, anti-K, anti-Jka, anti-N and anti-S. CONCLUSION: The transfusion of tnatched blood is essential for chronically nlultitransfused patients in order to avoid alloimmunisation. Considering high frequency of anti E in our hospital, it is advisable to genotype patients and n1atch the red cell unit for E antigens in multiply transfused thalassaemia patients.